Possible Augmentive Effect of Antioxidant Vitamin C in Patients with Essential Hypertension Treated with Amlodipin or Enalapril - A. Al-Rikaby, Maitham; J. Al â€“ Shamma, Kasim; A. Majeed, Ibrahim; SH.Hamondi, Saad (Iraqi Journal of Pharmaceutical Sciences, 2017)
Hypertension is identified as one of the most significant risk factors for cardiovascular diseases (CVDs). There is growing evidence showing that oxidative stress plays a major role in hypertension. Increased production of reactive oxygen species and decrease bioavailability of antioxidant have been demonstrated in experimental and human hypertension. The present study was directed to determine the beneficial effect of the antioxidant vitamin C in patients with essential hypertension treated with the calcium channel blocker (amlodipine) or with the angiotensin converting enzyme inhibitor (enalapril). Ninety six patients (50 females and 46 males) with essential hypertension and treated with amlodipine or enalapril, age (50.43 Â± 0.55 year) were participated in this study and divided in to: Twenty five patients received amlodipine 5mg tablet once daily (group 1), twenty five patients received the same dose of amlodipine plus 500mg of vitamin C tablet twice daily (group 2), twenty three patients received enalapril 5 mg tablet once daily (group 3), and twenty three patients received the same dose of enalapril plus 500mg of vitamin C tablet twice daily (group 4). Twenty apparently healthy subjects (11 females and 9 males) also participated in this study as control group (group 5). All patients were treated and followed up for one month. The mean blood pressures were measured for each patient before treatment and one, two, three and four weeks after treatment. Serum malondialdehyde (MDA), lipid profile, electrocardiogram (ECG) parameters and heart rate were measured for each patient before treatment and two and four weeks after treatment. The addition of vitamin C to amlodipine or enalapril treated patients had resulted in a significant (p<0.05) lowering effect on mean blood pressure after two, three and four weeks. On the other hand, the addition of vitamin C to amlodipine or enalapril treated patients had resulted in a significant lowering of serum MDA after two and four weeks of treatment. While there was no significant change in lipid profile or ECG parameters and heart rate of patients in group two and four after two and four weeks of vitamin C treatment as compared to their values at zero time and to patients in group one and three respectively. The study indicates that oxidative stress may have a significant role in essential hypertension, and addition of the antioxidant vitamin C to antihypertensive drugs used in this study can give a good blood pressure lowering effect and good protection against lipid peroxidation. Key words: Antioxidant ,Vitamin C, Essential Hypertension, Amlodipin , Enalapril